Penarikan Royalti Hak Cipta Sebagai Wujud Jaminan Fidusia Berdasarkan Hukum Positif di Indonesia - Kaina Medita; Tasya Safiranita; Rika Ratna Permata (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
The development of human civilization has given birth to a creative economy that is developing simultaneously. Copyright is one type of Intellectual Property that is given to creators and other parties who have rights to their creations to utilize exclusivity both economically and morally. Indonesian laws and regulations have been able to adjust to economic developments. However, in its implementation there are still gaps in terms of the withdrawal of copyright royalties as objects of fiduciary guarantees. This study aims to determine and identify the optimization of regulations for the implementation of copyright royalties as fiduciary guarantees based on positive law in Indonesia. This study was conducted using a normative juridical approach method, by conducting research through literature as the main research material. Based on the research conducted, it was found that although regulations have regulated copyright to be used as objects of fiduciary guarantees, there needs to be optimization of regulations and collaboration between the government and related institutions along with the development of the creative industry era.